From english teachers’ perceptions: English learning demotivating factors for Indonesian University students - Saifullah, Saifullah (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
Students’ demotivation is a crucial issue in EFL context that has not yet received sufficient research particularly in higher education level. In Indonesia English as a foreign language context, students’ demotivation in language learning is mostly addressed based on students’ perceptions. The purpose of the current study is to examine Indonesian university EFL teachers’ perceptions of factors demotivate students to study English at university level in Indonesia.  To collect the qualitative data, five teachers from English study program were involved in a semi-structured interviews with additional follow-up questions to further explore the raised concerns. These teachers were asked to understand their perceptions and experiences on what factors demotivate their students to study English. Seven demotivating factors were identified in teachers’ perception that demotivate students to study English: students’ attitudes toward English, students’ past experience, peers proficiency, teachers’ workload, classroom availability, hot and suffocating classroom, and technological facilities. This study has some implications for higher education policy makers, institutional authorities, EFL students, and EFL teachers in particular.